2023
DOI: 10.1002/mds.29515
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Parkinson's Disease–Specific MicroRNA Signature in Nasal and Oral Swabs

Patricia Schließer,
Felix L. Struebing,
Bernd H. Northoff
et al.

Abstract: BackgroundBiomaterials from oral and nasal swabs provide, in theory, a potential resource for biomarker development. However, their diagnostic value has not yet been investigated in the context of Parkinson's disease (PD) and associated conditions.ObjectiveWe have previously identified a PD‐specific microRNA (miRNA) signature in gut biopsies. In this work, we aimed to investigate the expression of miRNAs in routine buccal (oral) and nasal swabs obtained from cases with idiopathic PD and isolated rapid eye move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Peripheral tissue miRNAs may be of significance as hsa-miR-1260a from PD patients nasal and buccal swabs was significantly increased as compared with healthy controls [38]. Interestingly, non-coding miRNAs, miR-134 and miR-141 downregulated CDNF levels in an experimental setting calling for clinical studies on the biomarker properties of these miRNAs [34].…”
Section: Tissue Samplesmentioning
confidence: 99%
“…Peripheral tissue miRNAs may be of significance as hsa-miR-1260a from PD patients nasal and buccal swabs was significantly increased as compared with healthy controls [38]. Interestingly, non-coding miRNAs, miR-134 and miR-141 downregulated CDNF levels in an experimental setting calling for clinical studies on the biomarker properties of these miRNAs [34].…”
Section: Tissue Samplesmentioning
confidence: 99%
“…Among the best-studied epigenetic mechanisms, microRNAs (miRNAs) are a group of small non-coding RNA molecules ( ∼ 22 nucleotides in length) that regulate gene expression at post-transcriptional level by binding specific mRNA targets. Many studies have demonstrated that miRNAs are critically involved in important biological processes in healthy and diseased conditions, including cancer, Alzheimer's disease, cardiovascular diseases, viral infections and diabetes [24][25][26][27][28][29]. Dysregulated expression of specific miRNAs can contribute to disease progression by affecting critical signaling pathways and gene networks.…”
Section: Introductionmentioning
confidence: 99%